A Element Of Traditional Dance Choreography From a Dancesport Perspective: A comparative Study between Traditional dance and Dancesport - Wibisono, Namira Allegra (Solah, 2026)
Traditional dance is one form of cultural expression that is structured around three core elements of choreography: wiraga (movement), wirama (rhythm), and wirasa (feeling or expression). These elements serve as the foundation for choreography and as markers of cultural identity in every performance. Meanwhile, dancesport emerges as a competitive branch of sport that emphasizes technique, precision, aesthetics, and partner communication. This article aims to analyze the relationship between the core elements of traditional dance and the principles of dancesport, while also examining the potential transformation of cultural values within a competitive arena. The study employs a qualitative descriptive approach through literature review, observation of performance phenomena, and comparative analysis of choreographic elements. The findings indicate that although traditional dance and dancesport differ in orientation—traditional dance prioritizing cultural values and dancesport focusing on competitive achievement—both strongly emphasize the harmonization of movement, rhythm, and expression. The adaptation of traditional choreographic elements creates opportunities for cross-cultural choreographic innovation and strengthens Indonesia’s cultural diplomacy through the performing arts in the global arena.